Physical Exercise and Immune System in the Elderly: Implications and Importance in COVID-19 Pandemic Period - Scartoni, Fabiana Rodrigues; Sant’Ana, Leandro de Oliveira; Murillo-Rodriguez, Eric; Yamamoto, Tetsuya; Imperatori, Claudio; Budde, Henning; Vianna, Jeferson Macedo; Machado, Sergio (Frontiers in Psychology, 2020)
Physical exercise is seen as the main ally for health promotion, preventing and protecting the organism from several diseases. According to WHO, there is a tendency of constant growth in the elderly population in the coming years. The regular practice of exercises by the elderly becomes relevant to minimize the deleterious effects of the aging process and to increase the fitness index. Recently, the world population started a confrontation against Corona Virus Disease (COVID-19), which is the most significant public health challenge globally. Although social isolation is a reasonable measure in an attempt to stop contamination by COVID-19, this measure has limited the ability of individuals to exercise outdoors or in gyms and health clubs, which increased the risk of developing chronic illnesses related to a sedentary lifestyle. The critical point is that the recent recommendations on exercise prescription to combat the potentially harmful effects of COVID-19 failure to adequately address resistance exercise interventions as home-based exercise strategy. Thus, in this paper, we discussed the physical exercise as medicine if the training status is enough to protect the elderly against COVID-19 infection, about the role of physical activity on immunosuppression. Possible risks for COVID-19 infection, and the old training methods, such as no-load resistance training as possible resistance exercise strategies and high-intensity interval training, as new proposals of home-based exercise interventions, could perform during the current COVID-19 pandemic.